2013
DOI: 10.1128/iai.01331-12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Carboxypeptidase B1 of Anopheles stephensi and Its Evaluation as a Target for Transmission-Blocking Vaccines

Abstract: Malaria is one of the most important infectious diseases in the world, and it has many economic and social impacts on populations, especially in poor countries. Transmission-blocking vaccines (TBVs) are valuable tools for malaria eradication. A study on Anopheles gambiae revealed that polyclonal antibodies to carboxypeptidase B1 of A. gambiae can block sexual parasite development in the mosquito midgut. Hence, it was introduced as a TBV target in regions where A. gambiae is the main malaria vector. However, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 43 publications
4
47
0
Order By: Relevance
“…Further studies suggested that transmission blocking activity could likewise be obtained by targeting the mosquito components that are needed for the successful development of parasite inside the mosquito vector. These mosquito specific candidates include aminopeptidase N and carboxypeptidase B1, which are also able to induce an antibody response that significantly inhibits parasite development6365. However, further studies are needed to strengthen the candidacy of these antigens as a potent target of transmission blocking malaria vaccines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies suggested that transmission blocking activity could likewise be obtained by targeting the mosquito components that are needed for the successful development of parasite inside the mosquito vector. These mosquito specific candidates include aminopeptidase N and carboxypeptidase B1, which are also able to induce an antibody response that significantly inhibits parasite development6365. However, further studies are needed to strengthen the candidacy of these antigens as a potent target of transmission blocking malaria vaccines.…”
Section: Resultsmentioning
confidence: 99%
“…Potent Pfs28 was expressed as a chimeric protein in combination with Pfs25 to enhance the transmission blocking activity53. Vector molecules such as carboxypeptidase B (CPB) and aminopeptidase N (APN) play an important role in the development of P. falciparum inside the mosquito and, therefore, are considered as TBV candidates62636465. These candidates are conserved and elicit transmission reducing antibodies6667.…”
Section: Potential Of Tbv Candidatesmentioning
confidence: 99%
“…Carboxypeptidase, a well-known hydrolytic enzyme involved in C-terminal peptide cleavage, was also found to be highly regulated after blood meal [53]. In mosquito, carboxypeptidase has not only been found to be involved in sexual development of malarial protozoan parasites [54], but also in the interaction between carboxypeptidase and DENV capsid protein in the salivary gland [23] and the midgut cells [55]. In addition, carboxypeptidase D has been continuously proven to be a receptor for duck hepatitis B virus [56].…”
Section: Discussionmentioning
confidence: 99%
“…Development of the vaccines that interrupt malaria transmission (VIMTs) was emphasized by the vaccine consultative group for countries that have passed the pre-elimination step and have proceeded to the global goal [10]. VIMTs are divided into various types; one type is the classical transmissionblocking vaccine that blocks the sexual parasite development by targeting the required effector molecules in the vector, including mosquito-based transmission-blocking vaccines with targets such as Anopheles gambiae aminopeptidase N-1 (AgAPN-1) [11], CPBAg1 (Carboxy Peptidase B1) [12,13], Trypsin [14], saglin [15], FREP 1 [16,17], and SGS1 [18]. APN-1 is a candidate molecule for which the blocking efficacy against Plasmodium falciparum in An.…”
mentioning
confidence: 99%
“…gambiae. Some glycoproteins, such as APN-1, are receptors for the lectin-similar structures of ookinete that trigger the attachment of ookinetes to the internal side of the epithelium and are essential for preceding the sexual development of parasite in the mosquito midgut [13,16,20].…”
mentioning
confidence: 99%